PEMBANGKIT LISTRIK RAMAH LINGKUNGAN BERTENAGA SURYA GUNA MEMENUHI KEBUTUHAN NELAYAN PANTAI MATRAS BANGKA - Hidayat, Rizal Tegu; Rollastin, Boy; Pranandita, Nanda (Machine : Jurnal Teknik Mesin, 2024)
Natural resources in the form of solar heat, can be used as an alternative to electricity generation by using a power plant tool in the form of solar panels. In certain areas there are still many who need a supply of electric power, for example in the Turun Aban Sungailiat Beach area, Bangka Belitung Islands Province. At that location there is no electric power supply at all, the fishermen at the Turun Aban Beach location often carry out the process of transporting catches at night conditions. Therefore, to meet their needs, these fishermen can use alternative power plants in the form of solar panels. This research examines the process of analyzing the performance of solar-powered power plants. The solar panel produces 115.28 watts of power in 1 day. The time required for charging the battery is 5.81 hours/day and the battery endurance time is 4.65 hours in 1 day.